Neighborhood Characteristics and Crime Specific Victimization Rates: A Sociological Analysis - Jones, Esther Celeste (1996)
This dissertation examines the influence of ecological, institutional, and cultural variables on neighborhood victimization rates of assault, burglary, and robbery in 30 urban neighborhoods. Ordinary least square regression analysis is sued to determine which variables are most predictives of these rates. Based on social disorganization theory, social control theory, and subculture of violence theory, an integrated model is developed. The integrated model includes elements of all three theoretical orientations, clearly indicating that crime is not unidimensional, and that different variables are predictive of specific types of crime at the neighborhood level. It was found that assault and robbery were best predicted by neighborhood levels of educational attainment and neighborhood stability. In addition Proportion Black had no effect on any of the crimes, while Southern region had a negative effect on robbery. Theoretical implications of the findings and direction for future research are discussed